دور نظم الجودة في إدارة المستشفيات (دراسة حالة الجراحات الآمنة بالمستشفيات المركزية بمحافظة الفيوم) The role of quality systems in hospital management A case study of safe surgeries in Central hospitals Fayom Governorate - سعودى، نادية عجمى حسان; توفيق، محمد حسن (معهد التخطيط القومى, 2026)
تهدف هذه الدراسة إلى التعرف على دور نظم الجودة في إدارة المستشفيات، ومدى مساهمتها في تحقيق الجراحات الآمنة داخل المستشفيات المركزية بمحافظة الفيوم، وذلك في ظل التحديات التي يشهدها القطاع الصحي من نقص الموارد البشرية، وتفاوت مستوى تطبيق معايير الجودة والسلامة داخل وحدات العمليات الجراحية. وتنطلق الدراسة من تحليل العلاقة بين نظم الجودة كمتغير مستقل (إدارة الجودة الشاملة، التدريب، معايير السلامة، إدارة المخاطر) وأنظمة الجراحات الآمنة كمتغير تابع (التخدير، فريق الجراحة، التعقيم، المعدات، قائمة التحقق الجراحي). اعتمدت الدراسة على المنهج الوصفي التحليلي، واستخدمت استمارة استبيان لجمع البيانات من العاملين بالمستشفيات المركزية: (أبشواي، طامية، سنورس، إطسا)، وتم تحليل البيانات لتشخيص التحديات والمعوقات، وتقييم مستوى تطبيق معايير الجودة والجراحات الآمنة. كما استندت الباحثة إلى مقابلات استطلاعية مع القيادات الطبية والمسؤولين في المستشفيات المركزية بمحافظة الفيوم. أظهرت النتائج وجود علاقة إيجابية قوية بين تطبيق نظم الجودة ومستوى الجراحات الآمنة، حيث تبين أن الالتزام بإجراءات التعقيم، وتدريب الأطقم الجراحية، وتطبيق قائمة التحقق الجراحية يسهم في تحسين مستوى الأمان وتقليل معدلات الأخطاء الجراحية. كما أوضحت النتائج وجود تفاوت في تطبيق معايير الجراحة الآمنة بين المستشفيات، نتيجة نقص الموارد البشرية، وضعف التدريب، ومحدودية التجهيزات الفنية في بعض الوحدات الجراحية. أوصت الدراسة بضرورة تعزيز التدريب المستمر للعاملين، وتوفير الموارد اللازمة لتطبيق معايير الجودة، وتفعيل نظم إدارة المخاطر، والاستفادة من تقنيات الذكاء الاصطناعي في متابعة العمليات الجراحية وتحسين جودة الخدمة، بما يسهم في رفع مستوى سلامة المرضى داخل المستشفيات المركزية بمحافظة الفيوم. This study aims to explore the role of quality management systems in hospital administration and to assess their contribution to achieving safe surgical practices in the central hospitals of Fayoum Governorate. The study is conducted considering the challenges facing the healthcare sector, including shortages in human resources and variations in the application of quality and safety standards within operating units. The research examines the relationship between quality management systems as an independent variable (Total Quality Management, training, safety standards, and risk management) and surgical safety systems as a dependent variable (anesthesia, surgical team performance, sterilization, equipment readiness, and the surgical safety checklist). The study adopts a descriptive analytical methodology and utilizes a structured questionnaire administered to staff members working in the central hospitals of Abshway, Tamiya, Senouris, and Itsa. Data was analyzed to identify challenges and barriers and to assess the level of compliance with quality and surgical safety standards. The researcher also conducted exploratory interviews with medical leaders and administrative personnel in Fayoum central hospitals. The findings reveal a strong positive relationship between the application of quality management systems and the level of surgical safety. The results indicate that adherence to sterilization procedures, continuous training of surgical teams, and the implementation of the surgical safety checklist significantly enhance patient safety and reduce surgical errors. The study also highlights variations among hospitals in the implementation of safe surgery standards, mainly due to staff shortages, limited training, and inadequate technical resources in some surgical units. The study recommends strengthening continuous training programs, providing necessary resources to apply quality standards, activating risk management systems, and utilizing artificial intelligence techniques to monitor surgical procedures and improve service quality, thereby enhancing patient safety in the central hospitals of Fayoum Governorate